Development of a Family Business in a Franchise System - Nagy, Adrián; Tobak, Júlia; Kun, Gergő (International Journal of Engineering and Management Sciences, 2017)
The purpose of this study was to examine that franchise as a form of enterprise in perspective to existing family businesses how can they operate this way. Why is this form better for them, what advantages it has? In this case an ice cream shop’s economic inidicators was examined which one is owned by a hungarian family in JászNagykun-Szolnok county who runs several shops like this. That is why this study made, to find out is that possible to run it sucsessfully and what costs does the newcomers in the franchise business network have to pay and how much is the time on the return of investments.